A New Occurrence of the Telluride of Gold and Silver - A. Eilers (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1873)
THE telluride of gold and silver, the " Tellurgold-silver" of Hausmann, and " Petzite" of other mineralogists, has been found in so few localities, that a late discovery of the mineral in a new locality may not be uninteresting. So far this mineral has been found in Europe only in a few mines in Transylvania, and in Hungary ; and in the United States in the Stanislaus Mine, in Calaveras County, California, in the Golden Rule Mine, Tuolumne County, California, and in a mine in Montana, the precise locality of which I have forgotten. The new locality referred to is at the Red Cloud Mine, Gold Hill District, Boulder County, Colorado.